2020
DOI: 10.1021/acs.organomet.9b00856
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Vinylidene Complexes Generated by Selective 1,2-Migration of P- and S-Substituents: Synthesis, Structures, and Dichromism Arising from an Intramolecular CH···O Hydrogen Bond

Abstract: Investigation of the vinylidene rearrangement of phosphorus-and sulfur-substituted internal alkynes at a ruthenium center unveiled selective 1,2-migration of P-and S-substituents and unexpected dichromatic behaviors of a part of the resulting vinylidene complexes. Reactions of [CpRu(dppe)Cl] and R 1 C CR 2 , where R 1 = alkyl, Ar and R 2 = P(O)(OR) 2 , P(O)R 2 , SR, SO 2 R, in the presence of NaBAr F 4 afforded the corresponding vinylidene complexes [CpRu{CC(R 1 )(R 2 )}(dppe)][BAr F 4 ], which were fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…When a reaction of complex 1aa-13 C α or 1ca-13 C α with PPh 3 was performed, alkyne A was obtained with exclusive selectivity, indicating that the P-substituent served as a migration group with >99% selectivity (entries 1 and 2). Thus, combined with our previous reports on the vinylidene rearrangements, 12 it is revealed that both forward and backward alkyne/vinylidene isomerizations are mediated by the selective migration of the P-substituents.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…When a reaction of complex 1aa-13 C α or 1ca-13 C α with PPh 3 was performed, alkyne A was obtained with exclusive selectivity, indicating that the P-substituent served as a migration group with >99% selectivity (entries 1 and 2). Thus, combined with our previous reports on the vinylidene rearrangements, 12 it is revealed that both forward and backward alkyne/vinylidene isomerizations are mediated by the selective migration of the P-substituents.…”
Section: Resultssupporting
confidence: 61%
“…In our preceding study, it was confirmed that the vinylidene rearrangements of S-substituted alkynes at 70 °C proceed via the exclusive 1,2-migration of the heteroatom group. 12 Thus, it seems that the present less selective migration in the case of the SPh-substituted complex is somewhat contradictory.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations